Left Frontal Lobe Contributions to Concept Formation: A Quantitative MRI Study of D-KEFS Sorting Test Performance - Fine, Eric M. (2008)
This study examined relationships between lobar volumes and performance on the D-KEFS Sorting Test, a standardized measure of concept formation. Participants included 89 subjects, 19 patients with probable Alzheimer's disease, 25 patients with frontotemporal dementia, 13 patients with semantic dementia, 12 patients with progressive nonfluent aphasia, 9 patients with probable progressive supranuclear palsy, 2 patients with possible progressive supranuclear palsy, and 9 healthy participants. We used BRAINS2 software to generate volumes of the right and left frontal, temporal, and parietal lobes. Multiple regression analysis indicated that, after controlling for Mini-Mental State Examination scores, intracranial volume, and demographic variables, only the left frontal lobe significantly predicted performance on the D-KEFS Sorting test.